The diagnosis and treatment for a patient with cancer of unknown primary: A case report - Hu, Hong; Pan, Qin; Shen, Jiaying; Yao, Junlin; Fu, Guoxiang; Tian, Fengjuan; Yan, Na; Han, Weidong (Frontiers in Genetics, 2023)
Background: The diagnosis and treatment of unknown primary cancer (CUP) is a huge challenge for clinicians. We describe a case in which the location of the primary lesion was successfully diagnosed and benefited from treatment according to the tumor type in this study. Case Report: In February 2022, a 74-year-old female was admitted to the department of medical oncology, Sir Run Run Shaw Hospital because of new lung and intestinal tumors after breast cancer surgery more than 9 years. Pathology after laparoscopically assisted right hemicolectomy revealed mucinous adenocarcinoma and pathological stage was pT2N0M0. The results of needle biopsy of lung masses suggested poorly differentiated cancer, ER (-), PR (-), HER-2 (-), combined with the clinical history did not exclude metastatic breast cancer. Sample of surgical pathology was needed to determine the origin of the tumor tissue, but the chest structure of the patient did not have indications for surgery. Analysis of tumor traceable gene expression profile prompted breast cancer. There was not a drug targeting site in NGS high depth sequencing. Paclitaxel-albumin and capecitabine supplemented with radiotherapy were selected as the treatment regimen by immunohistochemistry (IHC), gene expression analysis and next generation sequencing (NGS) analysis. The efficacy evaluation was partial remission (PR) after 4 cycles of chemotherapy and 2 cycles of chemotherapy combined with radiotherapy. Conclusion: This case emphasized the importance of accurate location of the primary tumor for patients to benefit from treatment which will provide a reference for the treatment decision of CUP tumor in the future.